ApoE: The role of conserved residues in defining function. (9th December 2014) - Frieden, Carl
Abstract The amino acid sequences of apolipoprotein E (apoE) from 63 different mammalian species have been downloaded from the protein database. The sequences were compared to human apoE4 to determine conserved and non‐conserved sequences of amino acids. ApoE4 is the major risk factor for the development of late onset Alzheimer's disease while apoE3, which differs from apoE4 by a single amino acid change at position 112, poses little or no risk for the development of this disease. Thus, the two proteins appear to be structurally and functionally different. Seven highly conserved regions, representing approximately 47 amino acids (of 299) have been found. These regions are distributed throughout the protein and reflect ligand binding sites as well as regions proposed to be involved in the propagation of the cysteine–arginine change at position 112 to distant regions of the protein in the N‐ and C‐terminal domains. Highly non‐conserved regions are at the N‐ and C‐terminal ends of the apoE protein.